# Primitive of x by Square of Cotangent of a x

Jump to navigation Jump to search

## Theorem

$\displaystyle \int x \cot^2 a x \ \mathrm d x = \frac {-x \cot a x} a + \frac 1 {a^2} \ln \left\vert{\sin a x}\right\vert - \frac {x^2} 2 + C$

## Proof

With a view to expressing the primitive in the form:

$\displaystyle \int u \frac {\mathrm d v}{\mathrm d x} \ \mathrm d x = u v - \int v \frac {\mathrm d u}{\mathrm d x} \ \mathrm d x$

let:

 $\displaystyle u$ $=$ $\displaystyle x$ $\displaystyle \implies \ \$ $\displaystyle \frac {\mathrm d u} {\mathrm d x}$ $=$ $\displaystyle 1$ Primitive of Power

and let:

 $\displaystyle \frac {\mathrm d v} {\mathrm d x}$ $=$ $\displaystyle \cot^2 a x$ $\displaystyle \implies \ \$ $\displaystyle v$ $=$ $\displaystyle \frac {-\cot a x} a - x$ Primitive of $\cot^2 a x$

Then:

 $\displaystyle \int x \cot^2 a x \ \mathrm d x$ $=$ $\displaystyle x \left({\frac {-\cot a x} a - x}\right) - \int \left({\frac {-\cot a x} a - x}\right) \ \mathrm d x + C$ Integration by Parts $\displaystyle$ $=$ $\displaystyle \frac {-x \cot a x} a - x^2 + \int \left({\frac {\cot a x} a + x}\right) \ \mathrm d x + C$ simplifying $\displaystyle$ $=$ $\displaystyle \frac {-x \cot a x} a - x^2 + \frac 1 a \int \cot a x \ \mathrm d x + \int x \ \mathrm d x + C$ Linear Combination of Integrals $\displaystyle$ $=$ $\displaystyle \frac {-x \cot a x} a - x^2 + \frac 1 a \left({\frac {\ln \left\vert {\sin a x}\right\vert} a}\right) + \int x \ \mathrm d x + C$ Primitive of $\cot a x$ $\displaystyle$ $=$ $\displaystyle \frac {-x \cot a x} a - x^2 + \frac 1 {a^2} \ln \left\vert {\sin a x}\right\vert + \frac {x^2} 2 + C$ Primitive of Power $\displaystyle$ $=$ $\displaystyle \frac {-x \cot a x} a + \frac 1 {a^2} \ln \left\vert{\sin a x}\right\vert - \frac {x^2} 2 + C$ simplifying

$\blacksquare$